2001
DOI: 10.1021/jp0029459
|View full text |Cite
|
Sign up to set email alerts
|

Night-time Atmospheric Loss Process for Unsaturated Aldehydes:  Reaction with NO3 Radicals

Abstract: The rate constants for the gas-phase reactions of the NO3 radical with a series of unsaturated aldehydes (acrolein, crotonaldehyde, trans-2-pentenal, trans-2-hexenal, trans-2-heptenal, and cis-4-heptenal) have been measured directly using a flow tube system coupled to a laser-induced fluorescence (LIF) detection system where the NO3 radical was monitored. The kinetic study was conducted in the temperature range from 298 to 433 K to investigate the temperature dependence of these reactions. This work is the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 33 publications
(70 reference statements)
6
45
5
Order By: Relevance
“…A study by Cabanas et al [11] on a series of trans-2-aldehydes found rate constants which almost double when one carbon atom is added to the chain. The rate constant for the reaction of NO 3 with trans-2-butenal, trans-2-pentenal, trans-2-hexenal and trans-2-heptenal are 1.02, 2.88, 5.49 and 9.59 10 À14 cm 3 molecule À1 s…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…A study by Cabanas et al [11] on a series of trans-2-aldehydes found rate constants which almost double when one carbon atom is added to the chain. The rate constant for the reaction of NO 3 with trans-2-butenal, trans-2-pentenal, trans-2-hexenal and trans-2-heptenal are 1.02, 2.88, 5.49 and 9.59 10 À14 cm 3 molecule À1 s…”
Section: Perspectivementioning
confidence: 99%
“…[6,7] As the knowledge of the rate constants for the reactions of organic compounds with this radical is important for determination of their atmospheric lifetimes, several studies have been carried out since then to extend the experimental kinetic database of VOC oxidation. [8][9][10][11][12][13][14][15][16] They often concerned oxygenated compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the study of the reactions of trans-2-pentenal trans-2-hexenal, trans-2-heptenal, n-pentanal, n-hexanal, n-heptanal with OH radical has been carried out recently by Albaladejo et al (2002) by means of PLP/LIF technique at room temperature and as a function of the total pressure. Cabañas et al (2001a, b) also studied the temperature dependence of the reaction of these saturated and unsaturated aldehydes with NO 3 using a fastflow discharge system with LIF detection. The relative rate of these three reactions may define the global distribution of products from the atmospheric oxidation of aldehydes under local conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Relative to summer, nights in winter are longer, colder and more humid, and biogenic VOC emissions tend to be smaller. This allows for a larger fraction of NO 2 to be oxidized to HNO 3 via the N 2 O 5 hydrolysis pathway (Cabañas et al, 2001;Wagner et al, 2013), and colder temperatures favor partitioning of nitrate to the particle phase (Stelson and Seinfeld, 1982). In winter, nighttime HNO 3 production can more efficiently compete with daytime photochemically driven production due to the low photolysis rates and hydroxyl radical concentrations (Wagner et al, 2013;Pusede et al, 2016).…”
mentioning
confidence: 99%